Establishment, characterization, and validation of novel porcine embryonic fibroblasts as a potential source for genetic modification - Park, Chi-Hun; Jeoung, Young-Hee; Zhang, Luhui; Yeddula, Sai Goutham Reddy; Park, Ki-Eun; Waters, Jerel; Telugu, Bhanu P. (Frontiers in Cell and Developmental Biology, 2022)
Fibroblasts are the common cell type in the connective tissue-the most abundant tissue type in the body. Fibroblasts are widely used for cell culture, for the generation of induced pluripotent stem cells (iPSCs), and as nuclear donors for somatic cell nuclear transfer (SCNT). We report for the first time, the derivation of embryonic fibroblasts (EFs) from porcine embryonic outgrowths, which share similarities in morphology, culture characteristics, molecular markers, and transcriptional profile to fetal fibroblasts (FFs). We demonstrated the efficient use of EFs as nuclear donors in SCNT, for enhanced post-blastocyst development, implantation, and pregnancy outcomes. We further validated EFs as a source for CRISPR/Cas genome editing with overall editing frequencies comparable to that of FFs. Taken together, we established an alternative and efficient pipeline for genome editing and for the generation of genetically engineered animals.